The association between workplace ostracism and knowledge-sharing behaviors among Chinese university teachers: The chain mediating model of job burnout and job satisfaction - Wang, Guang-Hui; Li, Jia-Hui; Liu, Hui; Zaggia, Cristina (Frontiers in Psychology, 2023)
Workplace ostracism is an important predictor of knowledge-sharing behaviors, but few studies have explored the mechanism of this influence in higher education. Based on conservation of resources theory, this study elucidated the roles of job burnout and job satisfaction as sequential mediators of the link between workplace ostracism and knowledge-sharing behaviors in a sample of 388 university teachers. The results of the study were analyzed via structural equation modeling (SEM). Higher knowledge-sharing behaviors was associated with lower workplace ostracism and lower job burnout and more job satisfaction. Furthermore, increased workplace ostracism was associated with more job burnout, but job satisfaction was not related to workplace ostracism. The relationship between workplace ostracism and knowledge-sharing behaviors were mediated by job burnout and was sequentially mediated by job burnout and job satisfaction. These findings help clarify the mechanisms underlying the association between workplace ostracism and knowledge-sharing behaviors in university teachers. The theoretical and practical implications of the findings are discussed.